Do Prospective Intent and Established Metrics Correlate with Journal Impact Factor in Musculoskeletal Physical Therapy Trials?: A Secondary Analysis of A Methodological Review. (3rd September 2022) - Riley, Sean P.; Swanson, Brian T.; Shaffer, Stephen M.; Sawyer, Steven F.; Cleland, Joshua A.
ABSTRACT: Objectives: To determine if there are any statistically significant associations between: 1) randomized clinical trials (RCTs) investigating physical therapy musculoskeletal interventions, 2) journal impact factor (JIF), 3) frequency of RCT citation, 4) whether prospective intent was identifiable, and 5) the Physiotherapy Evidence Database (PEDro) scores. Methods: MEDLINE indexed RCTs addressing musculoskeletal interventions published between January 2016 and July 2020 in physical therapy journals were included. Two blinded reviewers identified the RCTs and extracted the variables of interest. Results: With a familywise alpha adjustment, there was no statistically significant correlation between JIF and number of citations ( rho = 0.187; p = 0.0280). Statistically significant weak positive correlations were identified between the JIF and prospectively registered RCTs ( rho = 0.240; p = 0.0046), JIF and PEDro scores ( rho = 0.250; p = 0.0031), and PEDro scores and prospectively registered RCTs ( rho = 0.335; p < 0.0001). Conclusion: The findings of this study suggest that JIF and PEDro scores may not be accurate measures of RCT quality. Failing to ensure that published RCTs followed their prospective intent and using bibliometrics that fail to accurately measure what they propose appears to create untrustworthy preprocessed resources for practicing physical therapists during the evidence-based practice process. Level of Evidence: 1a